Preparation and performance of 0.5Li2MnO3·0.5LiNi1/3Co1/3Mn1/3O2 with a fusiform porous micro-nano structure. Issue 41 (26th September 2016) - Wang, Gang; Wang, Xianyou; Yi, Liling; Yu, Ruizhi; Liu, Meihong; Yang, Xiukang
Abstract : Fusiform porous micro-nano 0.5Li2 MnO3 ·0.5LiNi1/3 Co1/3 Mn1/3 O2 has been synthesised as a cathode material for high performance lithium ion batteries. Abstract : A new lithium-rich layered cathode material 0.5Li2 MnO3 ·0.5LiNi1/3 Co1/3 Mn1/3 O2 with a porous fusiform micro-nano structure has been successfully synthesized via a facile co-precipitation method followed by high temperature calcination. X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy (EDXS) are used to characterize the chemical composition, structure, morphology and elemental distribution of the as-prepared lithium-rich layered material. It can be found that the as-prepared material presents a fusiform morphology and consists of interconnected nanosized subunits with a highly porous structure. The electrochemical measurements reveal that the material can deliver a high initial discharge capacity of 294.8 mA h g −1 and an excellent capacity retention of 87.1% after 200 cycles at 0.5C between 2.0 V and 4.6 V. In particular, even at a high rate of 10C, the material can still deliver a high discharge capacity of 139.5 mA h g −1 . The excellent electrochemical performances can be ascribed to the unique fusiform porous micro-nano structure, which can facilitate the diffusion of lithium ions and enhance the structural stability of the lithium-rich layered cathode materials.